From Theory to Practice - Žic Fuchs, Milena (Array, 1997)
The aim of this keynote was to show how theoretical constructs from Cognitive Linguistics could be applied in the teaching of English and in textbook writing. Special emphasis was put on the lexical inventory of English and Croatian and their subsequent differences, which become especially apparent if viewed from notions implicit in Prototype Theory.